SARS-CoV-2 antibody response after mRNA vaccination in healthcare workers with and without previous COVID-19, a follow-up study from the University Hospital in Krakow, Poland - Owsianka, Izabella; Pac, Agnieszka; Jachowicz, Estera; Gutkowska, Karolina; Szczuciński, Wiktor; Maziarz, Barbara; Sochacka-Tatara, Elżbieta; Heczko, Piotr; Sydor, Wojciech; Żółtowska, Barbara; Wójkowska-Mach, Jadwiga (Frontiers in Immunology, 2023)
Introduction: Healthcare workers (HCWs) from the beginning of the pandemic have been at risk of exposure to SARS-CoV-2, so they were vaccinated as first. Objectives The purpose of the study was to determine the level of antibodies against SARS-CoV-2 in HCWs before and after vaccination with mRNA preparations according to previous COVID- 19. Patients and Methods The HCWs from the University Hospital in Krakow completed two surveys: the baseline survey before receiving the first dose of vaccine (in January 2021) and the follow-up survey in June 2021. In parallel, two blood samples were collected from each participant at baseline and at follow-up. Total anti-SARS-CoV-2 antibody levels were measured using the ECLIA technique. Results At baseline, 41.1% of HCWs had positive antibody test results, and at follow-up, the vaccinated HCWs had almost 100 times higher antibody levels than the unvaccinated HCWs. Participants under 30 years of age had significantly higher antibody levels in June than older HCWs. Among participants with positive antibody test results in January, HCWs who had experienced asymptomatic COVID-19 had more than five times higher antibody levels in June than HCWs self-reported severe COVID-19. In total, 86.9% of HCWs received Comirnaty or Spikevax. The incidence rate of COVID-19 in the unvaccinated vs. vaccinated group was 13 times higher., 20.5% and 1.9% respectively. Conclusions These results confirm the effectiveness of vaccination in the prevention of COVID-19 in HCWs. It is worth getting vaccinated regardless of previous infection. Furthermore, vaccination among HCWs under 30 years of age induced more effective antibody production compared to older individuals.